Detection of Theileria orientalis Genotypes from Cattle in Kyrgyzstan - Ozubek, Sezayi; Ulucesme, Mehmet Can; Cirak, Veli Yilgor; Aktas, Munir (Mdpi, 2022)
The ikeda and chitose genotypes of Theileria orientalis, which for many years were thought to be benign, cause a disease that results in significant economic losses in the cattle industry. This study was carried out in order to determine the genotypes of T. orientalis in cattle in Kyrgyzstan, and 149 archived DNA samples known to be T. orientalis were analyzed by the PCR amplification of the major piroplasm surface protein (MPSP) gene region. Single-Strand Conformation Polymorphism (SSCP) analysis was performed to uncover the nucleotide changes in the archived DNA samples, and 15 samples showing different band profiles were subjected to sequence analysis. As a result of the sequence analysis, it was seen that the samples belonged to the buffeli and chitose A genotypes. In order to identify mixed genotypes, PCR was performed using primers specific for these genotypes, and buffeli (type 3), chitose (type 1) and buffeli+chitose were found to be positive in 26.2%, 2% and 71.8% of samples, respectively. As a result of this study, we showed the presence of buffeli (type 3) and chitose (type 1) genotypes of T. orientalis in cattle in Kyrgyzstan. Comprehensive epidemiological studies are needed to understand the clinical infections caused by the pathogenic chitose A and to determine the geographical distribution and different genotypes of T. orientalis.
Keywords: Theileria orientalis; genotype; cattle; PCR